Garden Birds and Wildlife - Toms, Mike and Sterry, Paul (China AA Publishing, 2010)
Suitable for wildlife watchers, this guide includes information from the BTO (British Trust for Ornithology), providing information about birds and wildlife in their gardens. Each entry is accompanied by photographs and illustrations to help with identification, regardless of the time of year or what the bird is doing.
Include Color Illustrations
Keywords: Gardening to Attract Birds